PENGEMBANGAN PROGRAM PERKULIAHAN UNTUK MEMBEKALI CALON GURU DALAM MERENCANAKAN KEGIATAN EKSPERIMEN FISIKA DI SEKOLAH MENENGAH - Utari, Setiya (2010)
This research R&D is aimed to get a draft of physics course program that equips students' tuition for prospective teachers to plan physics experiment activities in high school. The background of this study was based on the survey activities, analysis of curriculum and analysis the experimental skills of the student in LPTK. Based on the analysis of the associated literature and survey of the perceived need to be provided with skills in planning activities including all the experimental skills such as designing experimental goal, designing measurement techniques, designing specification of measuring instruments, designing experimental procedures, and obtained information from Internet browsing. The program tests are conducted in two stages, in the early stages we need to show that the ability with which the student was trained is a dependent variable on the ability to plan physics experiments activities in school. The second phase of testing is done by developing a rating scale to further test, the path significance relations, between the ability with which the student was trained and the ability to plan experimental activities. Experimental results show skill to obtain information through the internet browsing activities has the greatest direct effect with a value of 0,381, and can provide an indirect effect through the skill to design measurement techniques and to desaign experimental purpose.The result show that skill of designing experimental purpose. The results show that the skill of Designing experimental purpose, designing measurement techniques, designinprocedures and the skill of obtaining information throught the internet browsing activities have significance value < 0,05 and tcount>ttable (t8;0,05=2,305).Based on the results, the skills of which students were trained have a meaningful relationship to the skill in planning experimental activities.